Unlocking ESG Value: The Role of Firm-level Cash Flow in Asia Pacific - Lau, Wei-Theng; Ab Razak, Nazrul Hisyam; Chang, Yik-Khoon; Ng, Sin-Huei (International Journal of Economics and Financial Issues, 2025)
Environmental, social, and governance (ESG) factors are increasingly recognized as critical to corporate sustainability and value creation. Such ESG concerns have also sparked extensive research interest among academia and investors. This study explores the relationship between ESG performance and firm value, emphasizing the moderating role of cash flow in the Asia Pacific region. Using ESG pillar scores for the years 2017-2023 from 14 countries, the panel data regression reveals a nuanced impact of ESG initiatives on the performance of about 2000 firms. Firms with strong cash flow consistently experience a positive value-enhancing effect from ESG efforts, while those with weaker cash flows often encounter a value-diminishing impact. The environmental pillar drives value enhancement predominantly in emerging markets, whereas the social and governance pillars demonstrate consistent positive effects across sub-regions under favorable financial conditions. These findings highlight the conditional nature of ESG’s influence, suggesting that financial health is a critical determinant of the effectiveness of ESG initiatives. This study underscores the need for integrating ESG considerations with firm-specific financial conditions to achieve sustainable value creation. It aims to contribute to the ongoing discourse on ESG by providing practical guidance tailored to the dynamics of the Asia Pacific market.